Isopycnal and diapycnal mixing parameterization schemes for submesoscale processes induced by mesoscale eddies. (August 2022) - Sun, Wenjin; Dong, Changming
Abstract: With continuous and rapid improvements in computing power, the ability of ocean numerical models to resolve mesoscale process gradually increased. Consequently, traditional mesoscale parameterization schemes are potentially no longer suitable, requiring new schemes for submesoscale processes (SMPs). Mesoscale eddies are widely distributed in the global ocean, and their interiors and edges are often accompanied by SMPs. As such, it is the aim of this study to parameterize these processes and provide a new SMP parameterization scheme for mesoscale eddy-resolving models. Submesoscale phenomena accompanying mesoscale eddies are simulated using the Coastal and Regional Ocean Community (CROCO) model at a horizontal resolution of 500 m. Based on the flux-gradient relationship, each component of the eddy diffusivity tensor is then diagnosed by using the Moore-Penrose pseudo-inverse method. The least-square fitting is then used to obtain a new parameterization scheme. The eddy diffusivity tensor is found to be a function of horizontal front strength, stratification, eddy depth, Coriolis parameter and Richardson number.